Pendekatan Malcolm Baldrige Criteria For Performance Excellent (Education Criteria) dalam Perancangan Sistem Pengukuran Kinerja Fakultas Teknik Univeritas Udayana menuju Sertifikasi AUN-QA - I Made Dwi Budiana Penindra; I Made Gatot Karohika (Jurnal Energi Dan Manufaktur, 2020)
The Faculty of Engineering, Udayana University is one of the faculties in Udayana University. The Faculty of Engineering has 5 departments that have a lot of interest. Currently, the Faculty of Engineering is preparing to support Udayana University in obtaining the Asean University Network - Quality Assurance (AUN-QA) certification which is targeted for a visitation in 2021. One of the supporters in obtaining this certification is that the Faculty of Engineering must have a performance measurement system. In this research using an integrated performance measurement system that designed through the Malcolm Baldrige Criteria For Performance Excellent (Education Criteria) approach which is integrated with several methods, namely IPMS in determining the Key Performance Indicator (KPI) which becomes a determining indicator of later performance. assisted by using the Analytical Hierarchy Process (AHP) method in giving the weight of each KPI. After the KPI has a weight, then a comprehensive scoring is carried out using the Objectives Matrix (OMAX) method so that an index number per period is generated which is the reference for the level of performance of the department, as well as a Traffic Light System (TLS) to find out which KPIs require improvement based on color. With the creation of an integrated performance measurement system, it is hoped that the Faculty of Engineering can make continuous improvements. The results showed that the Performance Indicator from the Faculty of Engineering in this period was 427.19 with 24 KPIs being measured. The Performance Indicator shows that the overall performance of the Faculty of Engineering is above average (300). Only 2 categories are in the red zone of 21%, namely Student Criteria (KPI 1 and KPI 4) and Management Criteria (KPI 18, KPI 19, and KPI 20). In the following year, the Faculty of Engineering must focus on the five KPIs so that later they can improve performance.